2009
DOI: 10.1007/s11300-009-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant of Foreign Direct Investment in ASEAN: A Semi-Gravity Approach

Abstract: ASEAN, Foreign direct investment, Gravity model, F000, F150, F210,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
(26 reference statements)
2
18
0
1
Order By: Relevance
“…Obviously, the increase of the real interest rates encourage capital costs to increase, it also means that the financial risks exist, so it will limit FDI flows into the region. The coefficient of inflation is negative, as expected, but not statistically significant, this finding is also consistent with the conclusion of Ismail (2009). As expected, the coefficient of financial development is positive but not statistically significant.…”
Section: Regression Methodology and Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Obviously, the increase of the real interest rates encourage capital costs to increase, it also means that the financial risks exist, so it will limit FDI flows into the region. The coefficient of inflation is negative, as expected, but not statistically significant, this finding is also consistent with the conclusion of Ismail (2009). As expected, the coefficient of financial development is positive but not statistically significant.…”
Section: Regression Methodology and Resultssupporting
confidence: 88%
“…Similarly, the coefficient of trade openness is positive and statistically significant. Studies Ismail (2009), Masron and Abdullah (2010) also confirmed the positive role of trade openness to attract FDI flows into the region. As expected, the coefficient of the political stability is positive and statistically significant.…”
Section: Regression Methodology and Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Hattari and Rajan (2009) showed that shorter distance between the countries, real sector variables, financial variables, and quality of institutions promote FDI. Ismail (2009) showed that shorter distance, common language, and land border promote FDI. Mitze, Alecke, and Untiedt (2010) showed that there are substitutive relationships between trade and outward FDI in Germany.…”
Section: Fdi and The Channel For International Transmissionmentioning
confidence: 99%